2016
DOI: 10.1074/jbc.m116.724070
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase 5 Inhibition Limits Doxorubicin-induced Heart Failure by Attenuating Protein Kinase G Iα Oxidation

Abstract: Phosphodiesterase 5 (PDE5) inhibitors limit myocardial injury caused by stresses, including doxorubicin chemotherapy. cGMP binding to PKG I␣ attenuates oxidant-induced disulfide formation. Because PDE5 inhibition elevates cGMP and protects from doxorubicin-induced injury, we reasoned that this may be because it limits PKG I␣ disulfide formation. To investigate the role of PKG I␣ disulfide dimerization in the development of apoptosis, doxorubicin-induced cardiomyopathy was compared in male wild type (WT) or dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 40 publications
6
42
2
Order By: Relevance
“…S1). It was recently reported that PKGI␣ Cys 43 disulfide bond formation increased in vitro PKGI␣ activity toward histone H1 but not RhoA (16). However, in contrast to those results, we found that Cys 43 oxidation did not increase PKGI␣ activity toward histone H1 (Fig.…”
Section: Oxidation Of Pkgi␣ Cys 43 Does Not Increase Kinase Activity contrasting
confidence: 57%
See 2 more Smart Citations
“…S1). It was recently reported that PKGI␣ Cys 43 disulfide bond formation increased in vitro PKGI␣ activity toward histone H1 but not RhoA (16). However, in contrast to those results, we found that Cys 43 oxidation did not increase PKGI␣ activity toward histone H1 (Fig.…”
Section: Oxidation Of Pkgi␣ Cys 43 Does Not Increase Kinase Activity contrasting
confidence: 57%
“…6A in Ref. 16). In our experience, it is very difficult to fully remove cAMP during PKG purification, especially from PKGI␣ (10,20,22), and in general, Western blotting is semi-quantitative and is not an accurate method to measure kinase activity.…”
Section: Pkgi␣ Is Not Activated By Cysmentioning
confidence: 99%
See 1 more Smart Citation
“…Two rats which died were from LYG, and thus DOX and LY294002 may have a synergistic function for causing myocardial injury. Cell death was reported when PI3K/Akt pathway was blocked by the PI3K inhibitor LY294002 [1]. The optimization is going to be performed in future, including one-time dosage, interval time and accumulated dosages.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…The anthracycline doxorubicin (DOX) is widely used for tumor therapy, but its wide use often leads to heart failure [1].…”
Section: Introductionmentioning
confidence: 99%